The Effect of Training and Work Motivation on Operator Performance During the COVID-19 Pandemic - Sepriandi, Hendy; Gultom, Simon; Dewi Puspita Sari, Eka; Artamevia, Sherina; Budhi Setiawan, Edhie; Chairrudin, Irwan (KnE Social Sciences, 2023)
This research was conducted on a quay container crane operator at KSO TPK Koja. The quantitative research method was collecting data on 28 questionnaires and using SPSS version 21 applications to analyze data. The study used the validity, reliability, normality and hypothesis test. This study aimed to identify the influence of training and work motivation on operator performance during the COVID-19 pandemic at KSO TPK Koja. The result of this study showed that training and work motivation have a positive influence on operator performance, but training had no significant effect on operator performance. In addition, work motivation had a significant influence on operator performance. Keywords: Training, Work Motivation, Operator Performance, COVID-19